La identificación de complementos directos e indirectos en español y polaco - Lisowska , Monika (Studia Romanica Posnaniensia, 2023)
The aim of this paper is to compare the methods of identifying the direct and indirect object in Spanish and Polish. From the author’s point of view, Spanish relies more on semantic methods, while Polish relies more on formal ones, especially those related to the category of case. As the article strives to demonstrate, the two approaches can be significant for the different interpretations of objects in both languages.